Mediamorphosis: A Systematic Literature Review - Winanti, Anastasia; Anindita, Jaka; Irwansyah, Irwansyah (Riviera Publishing, 2023)
Mediamorphosis took place long before this term was conceptualized, and it continues to evolve with the development of communication and information technology. Based on a systematic literature review of selected articles, it is known that media metamorphosis has led to adaptation, updates, and innovations in research methodology, digital media development, communication message packaging, and the mechanisms related to media. Based on previous research, the concept of mediamorphosis provides a broad space for in-depth interdisciplinary studies on technology-mediated communication and its impact on human transformation. The review also suggests that mediamorphosis presents both challenges and opportunities for media practitioners, requiring a focus on ethics, the humanization of media, and critical thinking skills. Further research is needed to explore the impact of mediamorphosis on society and to develop strategies for navigating the evolving media landscape.